Academic and Professional Writing: The Professional Foundations - Roe, Peter J. (Journal of Modern Languages, 2017)
This paper sets out the main working assumptions which helps to shape the design and practical realities of the proposed writing programme to be offered by the Pusat Bahasa of the University of Malaya, both on and off campus in the second half of 1994. The study considers the rules of discourse in the community for which the student writers are producing text. These rules, not the student's own, become the standards for teaching and evaluating writing for the class.